(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases not associated with alcohol consumption. In recent years, special attention has been paid to the molecular genetic mechanisms of NAFLD pathogenesis, including the role of diagnostic genes. The article discusses the main genes associated with the development and progression of NAFLD, their diagnostic value, as well as the prospects for the use of genetic markers in clinical practice.